Knowledge and preventive behaviour among pregnant women with latent toxoplasmosis in Malaysia - Ahmad N; Emelia Osman; Abdul Ghani NA; Leong, WY; Arzaee MZ; Seow, YY; Dol Bahar S; Wan Yahya WNN; Mustapha N; Vadiveel Y (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Latent toxoplasmosis could induce various hormonal and behavioural perturbations in infected hosts. We aimed to study the latent seroprevalence of Toxoplasma gondii (T. gondii) and the relationship between infection, knowledge and behaviour among 400 pregnant mothers. Plasma samples were tested for the presence of T. gondii IgG antibodies while a structured questionnaire was used to record respondents’ socio-demographic characteristics, general information and knowledge on plausible risk factors, symptoms, timing of infection, and preventive knowledge and behaviour regarding toxoplasmosis. The seroprevalence of latent toxoplasmosis among respondents was at 31.8%. This study indicated that 69.5% of them had poor knowledge of toxoplasmosis but most of them (99.8%) practised preventive behaviours. Multiple logistic regression analysis showed that pregnant women with low education levels (aOR: 1.91, 95% CI 1.18, 3.10; p = 0.008) and past medical history (aOR: 2.32, 95% CI 1.32, 4.06; p = 0.003) were both twice as likely to have anti-T. gondii IgG seropositivity. Besides, women who were unsure regarding the transmission mode of the disease via blood transfusion were four times more likely (aOR: 3.93, 95% CI 1.54, 10.01; p = 0.004) to have chronic toxoplasmosis seroprevalence. Women who were unsure regarding the necessities of avoiding stray cats had aOR of 0.42 (95% CI 0.24, 0.71, p = 0.001) for chronic toxoplasmosis seroprevalence. Translating the knowledge on toxoplasmosis into the practice of preventive behaviour via a health education programme is crucial in reducing the risk of disease transmission especially among pregnant women.